Latar Belakang Ketertarikan Tokoh Watashi terhadap Tokoh Rokuzoo dalam Cepen Haru no Tori - Hera, Berlinda; Rahmah, Yuliani; Noviana, Fajria (Program Studi Sastra Jepang, Fakultas Ilmu Budaya, Universitas Diponegoro, 2016)
This thesis is a research of a short story, Haru no Tori by Kunikida Doppo which was published on 1904. Haru no Tori means The Spring Bird. Haru no Tori is a story about 11 years old boy named Rokuzoo, who’s got a mental disorders, which makes a teacher, Watashi, is interested by Rokuzoo’s pathetic life. This research is made for answering 2 main questions, such as: 1) to know the structure of Haru no Tori short story, and 2) to know why is Watashi interested on Rokuzoo’s life. The method that will used by the author of this thesis is structural method by Greimas. Greimas’s method is using two methods, they are actancial scheme and the functional structure. The methods used to facilitate the author to determine the storyline and different points of view, so the author will know what makes Watashi interested in Rokuzoo’s life from Haru no Tori. The results of this research by actancial scheme and structural method by Greimas are 14 of actancial schemes, 5 of functional structure, and one main actan which is the main core of Watashi’s interest on Rokuzoo’s life.So, the conclusions of this research are; 1) because Watashi is a teacher, he thinks he needs to do something to help Rokuzoo’s pathetic life by giving Rokuzoo a better education. 2) because Watashi feel so grateful by the kindness of Tanuguchi who lets Watashi stay in a rented room for a living place. 3) besides, Watashi is always interested to Rokuzoo’s strange fondness on bird.